A decision support system for a vendor managed inventory model of a single product distributed over M identical retail chain stores - Chua, Samuel Sy (Animo Repository, 2004)
Consumer buying decision is an important element of a company's effort to maximize market potential. The background of the study is a given scenario that a vendor-managed inventory (VMI) model is used to operate the inventory logistics of consigned products over a retail chain store network of identical size and characteristic. The study primarily introduces the use of a decision support system (DSS) method in coming up with a tool to improve the operations of the store network, through quantitative reports that guide the decision maker. A key issue discussed in this study is the use of probabilistic demand behavior of a consumer, based on the demographic segmentation of consumers in the respective area of coverage of individual retail chain stores. In completion of the study, two major DSS-VMI guidelines are derived and implemented. The first set are guidelines on how to device consumption plans for initial inventory distribution And the second set are guidelines for periodically evaluating in terms of a financial perspective the inventory status for the event of inventory reallocation, wherein a monthly scheme of evaluation was tested to be more effective based on the two sample companies used in the study. Finally, a detailed representation of a VMI system on leaseback or consigned scenario and additional information on consumer behavior, DSS, operations research, statistics and simulation are discussed in this study.